2021
DOI: 10.3390/sym13040552
|View full text |Cite
|
Sign up to set email alerts
|

Symmetries for Nonconservative Field Theories on Time Scale

Abstract: Symmetries and their associated conserved quantities are of great importance in the study of dynamic systems. In this paper, we describe nonconservative field theories on time scales—a model that brings together, in a single theory, discrete and continuous cases. After defining Hamilton’s principle for nonconservative field theories on time scales, we obtain the associated Lagrange equations. Next, based on the Hamilton’s action invariance for nonconservative field theories on time scales under the action of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…In this section, we establish the criteria for the transformation of Noether symmetries [16,17]. The first observation we make is that, according to Equation (3), we define the generalized nonpotential force…”
Section: Complex Noether Symmetriesmentioning
confidence: 99%
“…In this section, we establish the criteria for the transformation of Noether symmetries [16,17]. The first observation we make is that, according to Equation (3), we define the generalized nonpotential force…”
Section: Complex Noether Symmetriesmentioning
confidence: 99%
“…The statistics of papers called for this Special Issue, related to published or rejected items, are as follows [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]: 26 total submissions, of which 15 were published (57.6%) and 11 rejected (42.3%). The authors geographical distribution is shown in Table 1, and it can be seen that the 38 authors are from 9 different countries.…”
Section: Statistics Of the Special Issuementioning
confidence: 99%
“…As the commanding height of science and technology, it greatly enriches the content of attack-defense confrontation in near space [1][2][3][4]. Aiming at the optimal penetration guidance problem of high-speed vehicles against a modified proportional guidance interceptor, this paper obtains the analytical solution of an optimal penetration strategy by introducing Hamilton's principle [5][6][7]. Hamilton's principle is based on the principle of minimum action, which indicates that the motion trajectory of an object in any time interval causes the action to obtain the extreme value.…”
Section: Introductionmentioning
confidence: 99%